(untitled) (Scientific journal of the Fergana State University, 2024)
Sports training helps to cope with emotional and mental stress, and suppress negative emotions that arise in adolescence. During times of stress, connections between cells weaken and break. Those who lead an active lifestyle, active and curious, easily overcome stressors. Exercise makes gray cells work better. This helps you quickly overcome emotions and stress and make informed decisions.